Densitometry of the optically magnified dried residues representing carbon microparticles as a simple and affordable technique for determining their concentrations in aqueous suspensions. (March 2018) - Gerashchenko, Bogdan I.; Sydorenko, Oleksii S.; Snezhkova, Elisaveta A.; Klymchuk, Dmytro O.; Nikolaev, Vladimir G.
Graphical abstract: Highlights: A new technique is proposed for determining the concentrations of carbon microparticles in aqueous suspensions. The technique is based on densitometry of the optically magnified (20×) dry residues composed of carbon microparticles. The technique is more sensitive than spectrophotometry of the aqueous suspensions of carbon microparticles. At least 0.2 μg/ml of carbon microparticles can be detected in micro-aliquots (14 μl). Abstract: In extracorporeal blood purification, such as hemoperfusion, activated carbon (activated charcoal) beads are commonly used as an adsorbent, but their judgment in terms of extent of microparticle release is of great importance since the microparticles may represent the risk of entering the bloodstream. To quantitatively assess the release of carbon microparticles (CMPs) in the samples of the aqueous perfusion medium, in which the beads have been perfused, the calibration procedure with different concentrations of CMPs is likely to be needed. For this purpose, carbon beads were mechanically crushed to a fine powder, whose microparticles (<10 μm) were then serially diluted in the aqueous medium within the wide range of concentrations (0.2–100 μg/ml). To test these concentrations of CMPs, the micro-aliquots of each dilution of suspended CMPs were dried on a surface of hydrophobic membrane and at the optical magnification of 20× the dry residues were than analyzed by measuring the sum of densities. This simple and affordable technique was shown to be considerably more sensitive than spectrophotometry of the aqueous suspensions of CMPs.